Malaysian Publication Contributions to the Field of Library and Information Science - Norhazwani, Y.; Zainab, A.N. (2007)
The paper (a) described the total number and spread of publications produced by Malaysian contributors in the field of LIS for the period 1965 and 2005; (b) identified the active authors and authorship pattern, (c) identified the affiliation status of Malaysian researchers; (d) the preferred channel of research publications; and (e) the subject areas covered by the published works in LIS. The sample of the study comprised all located publications in the field of LIS by Malaysian authors published in Malaysia and abroad. Data was collected from LIS related online databases; online public library catalogues of selected libraries in Malaysia and Malaysian LIS journals. The data used in this study comprised 1045 publications which were based on accessible literature only. The results indicated (a) Malaysian LIS authors preferred publishing in journals (511, 48.9%), followed by conference papers (474, 45.4%), books (31, 2.9%) and book chapters (29, 2.8%); (b) even though the publication distribution fluctuated the moving average depicted a steady incremental trend over the 41-year period, (c) a total of 506 Malaysian authors contributed to the 1045 publications and 309 authors are one-time publishers, while the rest published between 2 and to as high as 52 publications; (d) the active Malaysian authors in LIS were affiliated to 131 institutions and the three dominant productive institutions were the National Library of Malaysia, University of Malaya Library and MLIS programme at the University of Malaya; (e) the subject areas written about in order of productivity were Management of library and information centres (30%), Information services (23%); Collection development and management (16%), ICT applications in LIS (14%), Information sources (10%), Organization of information (5%) and Legal issues in LIS (2%). The results revealed the areas actively written about, the productive authors and institutions. It highlights the areas which needed improvements and expansion in the field.